Transactional Relationships Between Latinos' Friendship Quality and Academic Achievement During the Transition to Middle School. (January 2016) - Sebanc, Anne M.; Guimond, Amy B.; Lutgen, Jeff
This study investigates whether friendship quality, academic achievement, and mastery goal orientation predict each other across the transition to middle school. Participants were 146 Latino students (75 girls) followed from the end of elementary school through the first year of middle school. Measures included positive and negative friendship quality, mastery goal orientation, and grade point averages (GPAs) at three time periods. In general, Latino adolescents showed stable academic achievement and did not decline in any of the measures from elementary school to middle school. Cross-lagged path analyses revealed a bidirectional and negative relationship between negative friendship quality and academic achievement across the transition to middle school. Positive friendship quality predicted mastery goal orientation decreases for girls. Both gender and bilingual status were analyzed and showed significant relations in our models. Results supported the social interaction perspective more than the social bonding perspective of friendship quality.